The The Role of 25-Hydroxy Vitamin D and Cartilage Oligomeric Matrix Protein(COMP) Serum in Knee Osteoarthritis - Khoriun Mukhsinin Putra (Indonesian Journal of Rheumatology, 2024)
Background. Osteoarthritis (OA) is a prevalent disease of themusculoskeletal system that affects over 528 million individuals worldwide,with 73% of those diagnosed being aged 55 or older. The knee joint is mostcommonly affected, along with the hip and hand joints. Vitamin D isessential for maintaining bone and cartilage metabolism. In chondrocytes,the presence of the vitamin D receptor (VDR) regulates the expression ofmetalloproteinase. The purpose of this investigation is to examine thecorrelation between vitamin D (25(OH)D) and cartilage oligomeric matrixprotein (COMP) serum in knee osteoarthritis. Methods. The cross-sectionalstudy was conducted by the Rheumatology Division at RSMH Palembang.Patients diagnosed with knee osteoarthritis based on the 1990 ACR criteriawere included.  The chemoluminescent immunoassay and the HumanCartilage Oligometric Matrix Protein ELISA Reagent were used to measurethe levels of vitamin D (25(OH)D) and COMP serum. Results. Thirtyparticipants took part in this study from July to December 2022. Accordingto this study, 33% had insufficiency and 67% had a deficiency of vitamin D.Spearman's Rho test shows that there is a strong negative correlationbetween vitamin D (25(OH)D) and COMP serum. Conclusion. Vitamin D(25(OH)D) and COMP serum levels were significantly correlated in kneeosteoathritis.